Production of carboxymethyl cellulose from sugar beet pulp cellulose and rheological behaviour of carboxymethyl cellulose - Togrul, H; Arslan, N (Elsevier Sci Ltd, 2003)
The sugar beet pulp cellulose was converted carboxymethyl cellulose (CMC) by etherification and the process of carboxymethylation was optimised with respect to the solvent medium, alkali concentration, sodium chloroacetate amount, temperature and time of reaction. The optimised product had a DS of 0.6670 and the optimum conditions for carboxymethylation were sodium chloroacetate amount of 3.0 g, an NaOH concentration of 30%, temperature of 70 degreesC, time of 360 min with isobutyl alcohol as the solvent medium. The flow behaviour of CMC from sugar beet pulp cellulose was determined using a rotational viscometer for concentration range of 10-30 kg/m(3), temperature range of 20-30 degreesC, and shear rate range of 3.24-64.8 s(-1). Newtonian, Bingham and power law models were applied to fit the flow behaviour of CMC solutions. The behaviour of CMC solutions was pseudoplastic and the flow behaviour of CMC solutions was found to be most adequately described by the power-law model. Concentration, temperature and shear rate affected the rheological properties. The temperature dependency of the consistency coefficient and the flow behaviour index was modelled using a Turian approach. Both the consistency coefficient and the flow behaviour index were sensitive to changes in temperature and concentration. The consistency coefficient varied between 0.0024 and 6.0162 whereas the flow behaviour index varied between 0.7017 and 0.9590. The flow behaviour index decreased with concentration and increased with temperature, while the opposite trend was observed with the consistency coefficient. The apparent viscosity decreased with increasing temperature and shear rate implying that CMC solutions studied behaved as shear thinning., The experimental data were fitted by mathematical models to allow prediction of the consistency coefficient, the flow behaviour index and the apparent viscosity as a function of temperature and concentration. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: sugar beet pulp; cellulose; carboxymethylation; carboxymethyl cellulose; rheology